Binder composition and application thereof, negative electrode material, negative electrode plate and lithium ion battery

By using a binder composition in the negative electrode material of a lithium-ion battery, the problem of volume expansion and conductivity reduction of silicon-based anode material during charging and discharging is solved, and the rate performance and long cycle stability of a lithium-ion battery are improved. Effect.

CN119463749AActive Publication Date: 2025-02-18SHANGHAI UNIV

Patent Information

Application Number
CN202411432063.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-18
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The volume expansion, mechanical damage, electrode and electrolyte interface problems and electrical conductivity of silicon-based negative electrode materials during charging and discharging, which affects the cycle life and safety of lithium-ion batteries.

Method used

Using a binder composition, including binder, conductor polymer and functional polymer, the negative electrode material used in lithium-ion batteries, improves mechanical properties and conductivity through dynamic hydrogen bonding and the addition of nanoparticles, and maintains the negative electrode. and the complete structure of the SEI membrane.

Benefits of technology

The rate performance and long cycle stability of lithium-ion batteries are improved, the volume expansion of the silicon-based negative electrode is suppressed, the fatigue damage of the adhesive layer is slowed down, and the complete structure of the negative electrode and SEI film is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463749A_ABST
    Figure CN119463749A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a binder composition and application thereof, a negative electrode material, a negative electrode plate and a lithium ion battery. The binder composition comprises the following components in parts by weight: 100 parts of a binder; 0.1 to 10 parts of conductor polymer; 0-20 parts of a functional polymer; the conductor polymer is selected from one or more of imine covalent organic framework polymers; the functional polymer is selected from one or more of polymers capable of forming dynamic hydrogen bonds with the binder and / or the conductor polymer. The binder composition is used for the silicon-based lithium ion battery, can maintain the complete structures of the negative electrode of the lithium ion battery and an SEI membrane, and can improve the electrochemical performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a binder composition and application thereof, a negative electrode material, a negative electrode sheet and a lithium ion battery. Background Art

[0002] In recent years, as the development direction of lithium-ion batteries is moving towards high energy density, high safety, high stability, etc., the industrial application of positive and negative active materials with high specific capacity has attracted widespread attention. Among them, compared with the theoretical specific capacity of 370mAh / g of traditional graphite negative electrode, the silicon negative electrode with a theoretical specific capacity of 4200mAh / g has been studied in detail. However, silicon-based materials will undergo large volume changes during the charging and discharging process, resulting in the destruction of the electrode structure and the shedding of active materials, thereby affecting the cycle life and safety of the battery. To solve this problem, researchers have carried out composite modification on the silicon-based materials themselves. For example, the negative electrode prepared by compositeing silicon and graphite in different ways has been initially applied. However, the silicon content of this type of silicon-carbon negative electrode is low, and the reversible specific capacity is only 400-450mAh / g. In order to meet the demand for higher energy density, it is necessary to further increase the silicon content of the silicon-carbon negative electrode so that its reversible specific capacity reaches 550-750mAh / g. In the practical application of high-silicon silicon-carbon negative electrodes, the functional modification of the binder, which can bind the active material, conductive agent and current collector together and inhibit volume expansion to a certain extent, has also attracted much attention. The binder not only affects the preparation process and cost of the electrode, but also plays an important role in the structural stability of the electrode, the transmission of electrons and ions, the formation of the solid electrolyte interface (SEI) film and the cycle life of the battery.

[0003] At present, commercial lithium-ion batteries mainly use polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), styrene-butadiene rubber latex (SBR), etc. as binders. They have good chemical stability, bonding effect and processability, but also have some disadvantages, such as poor high temperature resistance, easy swelling in electrolyte, poor electronic and ionic conductivity, etc.

[0004] The improvement of ion conductivity can be achieved through the following two methods: (1) adding an electrolyte expansion unit to absorb electrolyte; (2) adding electron-rich groups or highly polar groups to utilize their Li + Strong affinity to promote ion transfer. For the first method, although it relies on the high ion conductivity (~10 -2 S cm -1 ) improves the ion transport capacity, but too high an expansion rate may destroy the stability of the electrode, and strong polar groups or electron-rich groups, such as ether bonds, sulfonyl groups, and cyano groups, are not compatible with Li + The interaction is strong.

[0005] Silicon-based negative electrode materials face volume expansion, mechanical damage, electrode-electrolyte interface problems and decreased conductivity, which puts forward certain requirements for a considerable proportion of binders in the negative electrode slurry. The commonly used silicon-based negative electrode binders have problems such as insufficient mechanical properties, poor conductivity and poor interface stability. The more important and less concerned problems are as follows:

[0006] Lithium ion diffusion limitation: Insufficient ionic conductivity of the binder will limit the diffusion rate of lithium ions inside the electrode, because lithium ions need to pass through the binder layer to enter or leave the active material particles. This may lead to an increase in the concentration gradient of lithium ions inside the electrode, affecting the charge and discharge rate and efficiency of the battery.

[0007] Degraded cycle performance: If lithium ions cannot pass through the binder layer quickly and effectively during the charge and discharge process, it may cause uneven volume expansion of the electrode, which in turn causes fatigue and instability of the electrode structure, thereby reducing the cycle stability and life of the battery.

[0008] Increased interfacial reactions: Insufficient ionic conductivity of the binder may lead to increased interfacial reactions between the electrode and the electrolyte. In particular, during the electrode charging and discharging process, local electrolyte concentration or dehydration may occur on the electrode surface, resulting in uneven formation of the SEI layer, thus affecting the cycle stability and safety of the battery.

[0009] Increased loss: Due to the limited diffusion rate of lithium ions inside the electrode, the battery may generate additional heat during the charging and discharging process, resulting in increased damage to the binder layer, which in turn affects the cycle life and safety of the electrode.

[0010] Decreased power performance: Due to the limited diffusion rate of lithium ions, the electron conduction and ion transmission channels inside the electrode may be blocked, resulting in a decrease in the power performance of the battery. Especially under high-rate charge and discharge conditions, the battery may not be able to provide sufficient power output. Summary of the invention

[0011] The purpose of the present invention is to overcome the problems of volume expansion, mechanical damage, electrode-electrolyte interface problems and decreased conductivity faced by silicon-based negative electrode materials in the prior art, and to provide a binder composition and its application, a negative electrode material, a negative electrode sheet and a lithium ion battery. The binder composition is used for lithium ion batteries (such as silicon-based negative electrode lithium ion) and can maintain the intact structure of the negative electrode and SEI film of the lithium ion battery during the charge and discharge process, thereby improving the rate performance and long cycle stability of the lithium ion battery.

[0012] In order to achieve the above object, the present invention provides a first aspect of a binder composition, which comprises, by weight:

[0013] 100 parts of binder; 0.1-10 parts of conductive polymer; 0-20 parts of functional polymer;

[0014] The conductive polymer is selected from one or more imine-based covalent organic framework polymers;

[0015] The functional polymer is selected from one or more polymers capable of forming dynamic hydrogen bonds with the binder and / or the conductor polymer.

[0016] The second aspect of the present invention provides an application of the binder composition of the present invention in a lithium ion negative electrode binder.

[0017] The third aspect of the present invention provides a negative electrode material, which contains a silicon-containing negative electrode active material, a binder and a conductive material, wherein the binder contains the binder composition described in the present invention.

[0018] A fourth aspect of the present invention provides a negative electrode sheet, comprising a current collector and a negative electrode material layer disposed on a surface of the current collector, wherein the negative electrode material layer comprises the negative electrode material described in the present invention.

[0019] A fifth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode comprises the negative electrode sheet described in the present invention.

[0020] Through the above technical solution, the adhesive composition of the present invention can improve mechanical properties, such as high peel strength, low resistivity, and excellent conductive properties.

[0021] The adhesive composition of the present invention is used as a binder for lithium-ion batteries (such as silicon-based negative electrode lithium-ion) to maintain the complete structure of the negative electrode and SEI film of the lithium-ion battery during the charge and discharge process, and improve the rate performance and long-cycle stability of the lithium-ion battery. It is speculated that in the adhesive composition of the present invention, the conductive polymer has a large number of -C=N- active sites, has ionic and electronic dual conductivity, forms a negative electrode material layer with the silicon-based negative electrode active material, improves electronic conductivity, ion transmission efficiency and induces the formation of a stable SEI film, inhibits the volume expansion of the silicon-based negative electrode during the charge and discharge process, slows down the fatigue damage of the adhesive layer, and can maintain the complete structure of the negative electrode and SEI film during the charge and discharge process.

[0022] As a preferred embodiment of the present invention, a functional polymer is added to form a hydrogen bond network with the binder and the conductor polymer to form dynamic hydrogen bonds, so that it is in extensive contact with the silicon-based negative electrode active material, thereby improving the electronic conductivity, ion transfer efficiency and inducing the formation of a stable SEI film, inhibiting the volume expansion of the silicon-based negative electrode during the charge and discharge process, slowing down the fatigue damage of the binder layer, and being able to maintain the integrity of the negative electrode and the SEI film during the charge and discharge process, which can further improve the rate performance and long cycle stability of the lithium-ion battery.

[0023] According to a preferred embodiment of the present invention, the binder composition also contains the nanoparticles of the present invention. The addition of nano-inorganic particles can enhance the stability of the electrode structure, enhance the interface stability between the electrode and the electrolyte, and achieve self-dissipation of internal stress generated by the expansion of silicon particles, thereby further improving the rate performance and long-cycle stability of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Graphs showing the charge specific capacity and coulomb efficiency of the batteries of Application Example 2 and Comparative Application Example 1 after 500 cycles;

[0025] Figure 2 This is a graph of the battery rate performance of Application Example 2. DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] In the present invention, the imine covalent organic framework (ImineCOFs) polymer is a type of covalent organic framework polymer formed by condensation of organic amine monomers and aldehydes and ketone monomers according to the Schiff base reaction principle. The main type is the imine bond (C=N) formed by the condensation of amines and aldehydes or ketones. The main chain of the imine covalent organic framework polymer contains a -C=N- functional group.

[0028] The first aspect of the present invention provides a binder composition, which comprises, in parts by weight:

[0029] 100 parts of binder; 0.1-10 parts of conductive polymer; 0-20 parts of functional polymer;

[0030] The conductive polymer is selected from one or more of the self-chain imine covalent organic framework polymers;

[0031] The functional polymer is selected from one or more polymers that can form dynamic hydrogen bonds with the binder and / or the conductor polymer. The binder composition of the present invention, as a binder, can improve mechanical properties, such as high peel strength, low resistivity, and excellent conductivity. It can improve the rate performance and long cycle stability of lithium-ion batteries, especially silicon-containing negative electrode lithium-ion batteries.

[0032] In the present invention, the weight proportion of the conductive polymer can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. According to a preferred embodiment of the present invention, the conductive polymer is 0.1-5 parts, which is beneficial to improve the mechanical properties and improve the conductive properties.

[0033] In the present invention, the weight proportion of the functional polymer can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts. According to a preferred embodiment of the present invention, the functional polymer is 1-10 parts, which is beneficial to improve the mechanical properties and improve the conductive properties.

[0034] According to a preferred embodiment of the present invention, the adhesive composition further contains nanoparticles, and the nanoparticles are 0.01-1 parts, for example, 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, which is beneficial to improve the mechanical properties and improve the conductive properties.

[0035] According to a preferred embodiment of the present invention, the nanoparticles are present in an amount of 0.01-0.5 parts.

[0036] In the present invention, nanoparticles refer to material particles with a diameter between 1 and 100 nanometers (nm). According to a preferred embodiment of the present invention, the material of the nanoparticles is selected from one or more of barium titanate, nanocellulose, aluminum oxide, boron nitride, silicon oxide, zirconium oxide and titanium dioxide, which is conducive to improving the rate performance and long cycle stability of lithium-ion batteries, and can improve the thermal stability of batteries. The addition of nanoparticles is conducive to improving the flexibility of the binder, and is also conducive to achieving the dissipation of internal stress caused by the volume expansion of silicon-based active materials.

[0037] According to a preferred embodiment of the present invention, the particle size of the nanoparticles is 1-100 nm, which is beneficial to improving the rate performance and long cycle stability of the lithium-ion battery and improving the thermal stability of the battery.

[0038] According to one embodiment of the present invention, the adhesive composition comprises, by weight: 100 parts of adhesive; and 0.1-10 parts of conductive polymer.

[0039] According to one embodiment of the present invention, the binder composition comprises, in parts by weight: 100 parts of a binder; 0.1-10 parts of a conductive polymer; and 0.01-1 parts of nanoparticles.

[0040] According to one embodiment of the present invention, the binder composition comprises, in parts by weight: 100 parts of a binder; 0.1-5 parts of a conductive polymer; and 0.01-0.5 parts of nanoparticles.

[0041] In the present invention, the binder composition contains both a conductive polymer and a functional polymer, which can further improve the rate performance and long cycle stability of the lithium ion battery. According to a preferred embodiment of the present invention, the binder composition comprises, by weight: 100 parts of a binder; 0.1-5 parts of a conductive polymer; and 1-10 parts of a functional polymer.

[0042] In the present invention, the binder composition further contains the nanoparticles of the present invention, which can further improve the rate performance and long cycle stability of the lithium ion battery, and can improve the thermal stability of the battery. According to a preferred embodiment of the present invention, the binder composition includes, by weight: 100 parts of a binder; 0.1-5 parts of a conductive polymer; 1-10 parts of a functional polymer, and 0.01-0.5 parts of nanoparticles.

[0043] In the present invention, there is no particular limitation on the type of the binder in the binder composition. The binders conventionally used for lithium ion negative electrodes in the art can be used in the present invention to achieve the technical effect of the present invention. According to a preferred embodiment of the present invention, the binder is selected from one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), sodium alginate (SA), polyamide (PAI), polyvinyl alcohol (PVA), polyethyleneimine (PEI) and polyimide (PI).

[0044] According to a preferred embodiment of the present invention, the functional polymer is selected from one or more of polyurea, polyethylene glycol, acrylamide, polyvinyl imidazole, tannic acid, phytic acid and chitosan quaternary ammonium salt, which is beneficial to improving the rate performance and long cycle stability of lithium-ion batteries.

[0045] In the present invention, the monomers used to synthesize the imine covalent organic framework polymer include organic amine monomers and aldehyde and ketone monomers. Preferably, the organic amine monomer is selected from one or more of p-3,3'-diaminobenzidine, phenylenediamine, benzene diamine, tetraphenylethylenetetramine, tetrakis(4-aminophenyl)methane, 1,3,5-tris(4-aminophenyl)benzene and aromatic diaminochiral pyrrolidine, and the aldehyde and ketone monomers are selected from one or more of cyclohexanehexanone, 1,3,5-trialdehydebenzene, 1,3,6,8-tetrakis(4-aldehydephenyl)pyrene, biphenyl dicarboxaldehyde, terphenyl dicarboxaldehyde and terephthalaldehyde.

[0046] For example, the monomers for synthesizing PHATN (polyhexazopyridine) are cyclohexanehexaone and 3,3'-diaminobenzidine.

[0047] For example, the monomers for synthesizing COF-LZU-1 are 1,3,5-trialdehydebenzene and p-phenylenediamine.

[0048] For example, the monomers for synthesizing COF-LZU-72 are 1,3,5-trialdehyde benzene and aromatic diamino chiral pyrrolidine.

[0049] For example, the monomers for synthesizing ILCOF-1 are 1,3,6,8-tetrakis(4-formylphenyl)pyrene and p-phenylenediamine.

[0050] For example, the monomers for synthesizing SIOC-COF-1 are tetraphenylethylene tetramine, biphenyl dicarboxaldehyde and terphenyl dicarboxaldehyde.

[0051] For example, the monomers for synthesizing TAPB-PDA-COF are 1,3,5-tri(4-aminophenyl)benzene and terephthalaldehyde.

[0052] For example, the monomers for synthesizing COF-300 are tetrakis(4-aminophenyl)methane and terephthalaldehyde.

[0053] For example, the monomers for synthesizing COF-320 are tetrakis(4-aminophenyl)methane and biphenyldicarboxaldehyde.

[0054] For example, the monomers for synthesizing 3d-Py-COF are tetrakis(4-aminophenyl)methane and 1,3,6,8-tetrakis(4-formylphenyl)pyrene.

[0055] According to a preferred embodiment of the present invention, the conductive polymer is selected from one or more of PHATN (polyhexazopyridine), COF-LZU-1, COF-LZU-72, ILCOF-1, SIOC-COF-1, TAPB-PDA-COF, COF-300, COF-320 and 3d-Py-COF, which is beneficial to further improve the rate performance and long cycle stability of lithium-ion batteries.

[0056] According to a preferred embodiment of the present invention, the conductive polymer is selected from at least two of PHATN, COF-LZU-1, COF-LZU-72, ILCOF-1, SIOC-COF-1, TAPB-PDA-COF, COF-300, COF-320 and 3d-Py-COF, wherein the content of any one conductive polymer is not less than 20wt% and not more than 80wt% of the total mass of the conductive polymer, and the use of two or more conductive polymers is beneficial to further improve the rate performance and long cycle stability of the lithium-ion battery.

[0057] According to a preferred embodiment of the present invention, the conductive polymer contains at least PHATN, and more preferably the content of PHATN is 40-60 wt % of the total mass of the conductive polymer.

[0058] In the present invention, the conductive polymer is a type of imine covalent organic framework polymer formed by condensation of organic amine monomers and aldehydes and ketone monomers according to the Schiff base reaction principle. There is no particular limitation on the source and preparation method of the conductive polymer, as long as the conductive polymer can be prepared. This is an exemplary description, but it does not limit the scope of the present invention. The present invention provides a polyhexaazine method, comprising:

[0059] (1) Weigh 5-10 parts of cyclohexanone octahydrate, 5-10 parts of 3,3'-diaminobenzidine, 50-150 parts of N-methylpyrrolidone (NMP), 1-6 parts of concentrated sulfuric acid and 300-500 parts of deionized water;

[0060] (2) Under an argon atmosphere, cyclohexanehexanone octahydrate, 3,3'-diaminobenzidine and NMP were mixed;

[0061] (3) adding a mixture of NMP and concentrated sulfuric acid, stirring and heating the mixture to react, separating and drying the mixture to obtain a brown polyhexaazanaphthalene (PHATN) COFs material; preferably, the heating conditions include: a temperature of 50-80° C. and a heating time of 5-30 h.

[0062] According to a preferred embodiment of the present invention, in step (3), a mixture of NMP and concentrated sulfuric acid is added under an ice bath.

[0063] The second aspect of the present invention provides an application of the binder composition of the present invention in a lithium ion negative electrode binder, preferably in a silicon-containing negative electrode binder. The binder composition of the present invention is used as a binder for lithium ion batteries (such as silicon-based negative electrode lithium ions) to maintain the intact structure of the negative electrode and SEI film of the lithium ion battery during the charge and discharge process, thereby improving the rate performance and long cycle stability of the lithium ion battery.

[0064] The third aspect of the present invention provides a negative electrode material, which contains a silicon-containing negative electrode active material, a binder and a conductive material, wherein the binder contains the binder composition described in the present invention.

[0065] In the present invention, the mass content of the silicon-containing negative electrode active material and the conductive material binder composition can be selected in a wide range, and the conventional amounts in the field can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, in the negative electrode material, the silicon-containing negative electrode active material is 80-100 parts, the binder content is 1-10 parts, and the conductive material content is 1-10 parts.

[0066] The adhesive composition of the present invention is particularly suitable for silicon-based negative electrode lithium ion binder, which can maintain the intact structure of the negative electrode and SEI film of the lithium ion battery during the charge and discharge process, and improve the rate performance and long cycle stability of the lithium ion battery; according to a preferred embodiment of the present invention, the silicon content in the silicon-containing negative electrode active material is not less than 5wt%, preferably not more than 45wt%.

[0067] According to a preferred embodiment of the present invention, the silicon-containing negative electrode active material is selected from silicon-carbon negative electrode materials.

[0068] According to a preferred embodiment of the present invention, in the silicon-carbon negative electrode material, the silicon content is 15-25wt%, and the carbon content is 75-85wt%.

[0069] According to a preferred embodiment of the present invention, the specific capacity of the silicon-containing negative electrode active material is 550-750 mAh / g.

[0070] In the present invention, there is no particular limitation on the type of conductive material. Conventional conductive materials in the art can be used in the present invention to achieve the purpose of the present invention. According to a preferred embodiment of the present invention, the conductive material is selected from one or more carbon-based conductive materials, preferably one or more of SP (Sup P, Sup C45, Sup C65, KS-6), acetylene black, Ketjen black, graphene and carbon nanotubes. In the embodiments of the present invention, Super P (Sup P) material is used as an example, but the protection scope of the present invention is not limited thereto.

[0071] A fourth aspect of the present invention provides a negative electrode sheet, comprising a current collector and a negative electrode material layer disposed on a surface of the current collector, wherein the negative electrode material layer comprises the negative electrode material described in the present invention.

[0072] A fifth aspect of the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode comprises the negative electrode sheet described in the present invention.

[0073] The present invention will be described in detail below through examples.

[0074] In the following examples, the peel strength parameters were measured using the 180° peeling performance tester model 5943 produced by INSTRON Instruments, Inc. of the United States. The specific test method is: cut the dried electrode into rectangular strips with a width of 15 mm and a length of 80 mm, fix the sample on the sample holder, and firmly adhere the surface of the electrode with the material with a 13 mm wide 3M tape. Then, at 50 mm min. -1 The electrode is slowly peeled off from the electrode at a speed of , and the pulling force used is collected and recorded.

[0075] The resistivity parameters are measured using the RST-8 four-probe tester launched by Guangzhou Four Probe Technology Co., Ltd., China. By applying force, an ohmic connection is created between the probes and the adhesive film to be tested. A constant current power supply is then used to pass a small current through the two probes at the two ends. A voltmeter is then used to accurately measure the voltage V between the two middle probes. Finally, the film resistivity of the corresponding sample to be tested can be calculated.

[0076] The polyacrylic acid raw material is the water-based adhesive LA136D produced by Sichuan Yindile Technology Co., Ltd.

[0077] The polyimide raw material is the water-based adhesive Tinctive T126 produced by Guangzhou Tinci High-tech Materials Co., Ltd.

[0078] Example 1

[0079] (1) Ingredients: 100 parts of polyacrylic acid binder, 3 parts of chitosan quaternary ammonium salt, 3 parts of tannic acid, 1 part of polyhexazoline, 0.1 part of nano-alumina (particle size of 80-100 nm), and 200 parts of deionized water;

[0080] (2) Dispersing polyhexaazine, nano-alumina, chitosan quaternary ammonium salt, and tannic acid in 100 parts of water to obtain a dispersion, and dispersing polyacrylic acid in 100 parts of water to obtain another dispersion; mixing the two dispersions, stirring for 3 hours, and then passing through a 400-mesh sieve to obtain an emulsion dispersion.

[0081] Example 2

[0082] (1) Ingredients: 100 parts of polyacrylic acid binder, 5 parts of chitosan quaternary ammonium salt, 5 parts of tannic acid, 5 parts of polyhexazoline, 0.5 parts of nano-alumina (particle size of 80-100 nm), and 200 parts of deionized water;

[0083] (2) Dispersing polyhexaazine, nano-alumina, chitosan quaternary ammonium salt, and tannic acid in 100 parts of water to obtain a dispersion, and dispersing polyacrylic acid in 100 parts of water to obtain another dispersion; mixing the two dispersions, stirring for 3 hours, and then passing through a 400-mesh sieve to obtain an emulsion dispersion.

[0084] Example 3

[0085] The method of Example 2 is followed, except that 10 parts of chitosan quaternary ammonium salt, 10 parts of tannic acid, 10 parts of polyhexazoline, and 1 part of nano-alumina are used, and the other conditions are the same as those of Example 2.

[0086] Example 4

[0087] The method of Example 2 is followed, except that an equal amount of nano-boron nitride (80-100 nm) is used to replace nano-aluminum oxide, and the remaining conditions are the same as those of Example 2.

[0088] Example 5

[0089] The method of Example 2 is followed, except that a polyimide adhesive is used instead of a polyacrylic acid adhesive, and the other conditions are the same as those of Example 2.

[0090] Example 6

[0091] The method of Example 2 is followed, except that the ingredients are: 100 parts of polyacrylic acid binder, 5 parts of chitosan quaternary ammonium salt, 5 parts of tannic acid, 5 parts of polyhexazoline, and 200 parts of deionized water; the other conditions are the same as those of Example 2.

[0092] Example 7

[0093] The method of Example 2 is followed, except that the ingredients are: 100 parts of polyacrylic acid binder, 5 parts of polyhexazoline, 0.5 parts of nano-alumina (particle size 80-100 nm) dispersion, and 200 parts of deionized water; the other conditions are the same as Example 2.

[0094] Example 8

[0095] The method of Example 2 is followed, except that the ingredients are: 100 parts of polyacrylic acid binder, 5 parts of polyhexazoline, and 200 parts of deionized water; the other conditions are the same as those of Example 2.

[0096] Example 9

[0097] The method of Example 2 is followed, except that 2 parts of COF-LZU-1 are used to replace 5 parts of polyhexazoline; the other conditions are the same as those of Example 2.

[0098] Example 10

[0099] The method of Example 2 is followed, except that 4 parts of COF-320 are used to replace 5 parts of polyhexazoline; the other conditions are the same as those of Example 2.

[0100] Embodiment 11

[0101] The method of Example 2 is followed, except that 5 parts of polyhexazoline are replaced by 5 parts of ILCOF-1; the other conditions are the same as those of Example 2.

[0102] Example 12

[0103] The method of Example 2 is followed, except that 3 parts of polyhexaazanaphthalene and 2 parts of COF-LZU-1 are used to replace 5 parts of polyhexaazanaphthalene; the other conditions are the same as those of Example 2.

[0104] Comparative Example 1

[0105] The method of Example 7 is followed, except that no polyhexazoline is added, and the other conditions are the same as Example 7.

[0106] Comparative Example 2

[0107] The method of Example 8 is followed, except that no polyhexazoline is added, and the other conditions are the same as Example 8.

[0108] Comparative Example 3

[0109] The method of Example 2 is different in that the ingredients are: 100 parts of polyacrylic acid binder, 5 parts of chitosan quaternary ammonium salt, 5 parts of tannic acid, 0.5 parts of nano-alumina (particle size of 80-100nm), and 200 parts of deionized water; the other conditions are the same as Example 2.

[0110] Application Example 1

[0111] This application example provides a negative electrode sheet and a lithium-ion battery including the negative electrode sheet. The preparation method of the negative electrode sheet and the lithium-ion battery including the negative electrode sheet is as follows:

[0112] S1. Preparation of negative electrode sheet:

[0113] The negative electrode active material is a silicon-carbon material of model SL650B1-SC produced by Nanjing Tianmu Pioneer, with silicon and carbon contents of 15% and 85% respectively and a reversible specific capacity of 650mAh / g.

[0114] Prepare an emulsion dispersion according to the method of Example 1, and add deionized water to dilute it to a solid content of 4 wt %. Weigh 100 parts, that is, 4 parts of the dry weight of the binder.

[0115] Weigh other ingredients according to the mass ratio of silicon-carbon material: Super P: binder dry weight = 93:3:4. Grind the silicon-carbon material and Super P evenly, add them into the binder diluent, disperse them into a uniform slurry, use a 200μm scraper to evenly scrape the slurry on the copper foil, put it into a vacuum oven at 80℃ and dry it for 8h, then cut the electrode into slices and put it into a vacuum oven at 80℃ and dry it for 8h, and put it into the glove box for use.

[0116] S2. Battery Assembly

[0117] The prepared negative electrode sheet was assembled into a CR2025 button cell in an argon-protected glove box with a metal lithium sheet as the counter electrode, a polypropylene microporous membrane (Celgard 2500) as the separator, and a 1 mol / L ternary electrolyte (1M LiPF6 EC / DEC (volume ratio 1:1) + FEC 10% (v)) as the electrolyte. The battery was sealed at 50 MPa and left to stand for 12 hours to obtain the lithium-ion battery.

[0118] Application Examples 2-12 and Comparative Application Examples 1-2 adopt the same preparation method as Application Example 1, except that the binder is replaced by the binder provided in Example 2-12 and the binder provided in Comparative Example 1-2, respectively.

[0119] A negative electrode sheet and a lithium-ion battery were prepared according to the methods of Application Example 1-12 and Comparative Application Example 1-2, and the following performance tests were performed:

[0120] Conductivity test

[0121] Add deionized water and stir to dilute the binder of the above embodiment and comparative example to a 2% solid content emulsion. Weigh 10g of the emulsion and pour it into a polytetrafluoroethylene culture dish with a diameter of 80mm. Place the culture dish in a constant temperature oven at 100℃ to dry. Cut the prepared adhesive film into a 5cm×5cm film, and then place it between two graphite plates. Use an electrochemical workstation to test the resistance at different temperatures through AC impedance, and then calculate the conductivity of the film at different temperatures through formula (1);

[0122] σ=t / R×S (1)

[0123] Where, σ is the proton conductivity (S / cm), t is the thickness of the proton exchange membrane (cm), R is the in-plane resistance perpendicular to the membrane surface (Ω), and S is the effective membrane area (cm 2 ), the conductivity test results are shown in Table 1.

[0124] Mechanical properties test

[0125] The negative electrode sheet was cut into strips of 15 mm × 80 mm, 3M transparent tape was pasted on one side of the coating layer, and the coating layer was peeled off in the 180° direction at a speed of 50 mm / min using a tensile testing machine, and the peeling stress was measured. The peeling stress was used as the basis for judging the bonding performance. The greater the peeling stress, the better the bonding strength of the adhesive. The mechanical properties test results are shown in Table 2.

[0126] The prepared battery was subjected to the following electrochemical performance tests on a blue electric tester:

[0127] Constant current charge and discharge experiment: the test voltage range is 0.0051.5V, the cycle test current density is 0.5C, 1C=1000mAh / g.

[0128] Rate performance: The battery was charged and discharged in cycles at currents of 0.1C, 0.5C, 1C, 2C, and 5C, with 10 cycles at each current density and then back to 0.1C for 10 cycles. The charge and discharge voltage range was 0.0051.5V.

[0129] Cycle stability: After activation and stabilization, the battery was charged and discharged at 0.5C for 150 cycles. Figure 1 The charge capacity and coulomb efficiency of the batteries of Application Example 2 and Comparative Application Example 1 after 500 cycles are shown in FIG. Figure 2 It is a battery rate performance diagram of Application Example 2, which together illustrate that the technical means of the present invention improves the rate performance and long-cycle stability of the lithium-ion battery.

[0130] The electrochemical test results are shown in Tables 2 and 3; in Table 3, the specific capacity at each rate is the average value of the specific capacity of 10 charges; the specific capacity retention rate is the ratio of the average value of the specific capacity of the last 10 cycles of 0.1C charging to the average value of the specific capacity of the first 10 cycles of 0.1C charging.

[0131] Table 1

[0132] serial number <![CDATA[Conductivity × 10 -4 (S·cm -1 ) <!-- 8 -->]]> Example 1 2.85 Example 2 3.61 Example 3 3.48 Example 4 3.40 Example 5 3.53 Example 6 3.29 Example 7 3.17 Example 8 3.21 Example 9 3.53 Example 10 3.60 Embodiment 11 3.50 Example 12 3.60 Comparative Example 1 2.31 Comparative Example 2 2.28 Comparative Example 3 2.52

[0133] Table 2

[0134]

[0135]

[0136] Table 3

[0137]

[0138]

[0139] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A binder composition, characterized in that: In parts by weight, it includes: 100 parts of binder; 0.1-10 parts of conductive polymer; 0-20 parts of functional polymer; The conductive polymer is selected from one or more imine-based covalent organic framework polymers; The functional polymer is selected from one or more polymers capable of forming dynamic hydrogen bonds with the binder and / or the conductor polymer.

2. The adhesive composition according to claim 1, wherein 0.1-5 parts of conductive polymer; and / or The functional polymer is 1-10 parts.

3. The adhesive composition according to claim 1 or 2, wherein The binder composition further contains nanoparticles, the nanoparticles are 0.01-1 parts, preferably 0.01-0.5 parts; The material of the nanoparticles is selected from one or more of barium titanate, nanocellulose, aluminum oxide, boron nitride, silicon oxide, zirconium oxide and titanium dioxide; preferably, the particle size of the nanoparticles is 1-100 nm.

4. The binder composition according to any one of claims 1 to 3, wherein The conductive polymer is selected from one or more of PHATN, COF-LZU-1, COF-LZU-72, ILCOF-1, SIOC-COF-1, TAPB-PDA-COF, COF-300, COF-320 and 3d-Py-COF; and / or The binder is selected from one or more of styrene-butadiene rubber, polyvinylidene fluoride, polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose, sodium alginate, polyamide, polyvinyl alcohol, polyethylene imine and polyimide; and / or The functional polymer is selected from one or more of polyurea, polyethylene glycol, acrylamide, polyvinyl imidazole, tannic acid, phytic acid and chitosan quaternary ammonium salt.

5. Use of the binder composition according to any one of claims 1 to 4 in a lithium ion negative electrode binder.

6. A negative electrode material, characterized in that: The negative electrode material contains a silicon-containing negative electrode active material, a binder and a conductive material, wherein the binder contains the binder composition according to any one of claims 1 to 4.

7. The negative electrode material according to claim 6, wherein In parts by weight, in the negative electrode material, the silicon-containing negative electrode active material is 80-100 parts, the binder content is 1-10 parts, and the conductive material content is 1-10 parts.

8. The negative electrode material according to claim 6 or 7, wherein The silicon content of the silicon-containing negative electrode active material is not less than 5wt%, preferably not more than 45wt%; Preferably, the silicon-containing negative electrode active material is selected from silicon-carbon negative electrode materials; Preferably, the silicon content is 15-25wt% and the carbon content is 75-85wt%; and / or The specific capacity of the silicon-containing negative electrode active material is 550-750 mAh / g.

9. A negative electrode sheet, comprising a current collector and a negative electrode material layer disposed on the surface of the current collector, characterized in that: The negative electrode material layer comprises the negative electrode material according to any one of claims 6 to 8.

10. A lithium ion battery comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, characterized in that: The negative electrode comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Compound binder of silicon-based negative electrode for lithium ion batteries and preparation method thereof

    CN107863535A

  • Water-based composite binder, battery pole piece and application of battery pole piece

    CN117727933A

  • Lithium ion battery binder, silicon-based negative plate containing same and preparation method of silicon-based negative plate

    CN118398820A

  • Covalent organic framework and its electochemical use

    US20240079591A1

Cited By

  • Binder, positive plate and battery

    CN121064783A

  • Non-fluorine positive electrode binder for lithium ion battery and positive electrode plate

    WO2026200241A1